Praktik Real Earning Management, Corporate Governance dan Nilai Perusahaan: Bukti Pada Industri Manufaktur di Indonesia - Supardi, Supardi; Ashari, Sidiq; Setyapurnama, Yudi Santara; Djasmanuddin, Djasmanuddin (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p02, 2022)
This study aims to examine the effect of real earnings management on firm value with corporate governance as a moderating variable. The data used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the fiscal year ending December 31, 2015 to 2019. The data collection technique is purposive sampling and comes from secondary data both from the IDX and from the website of each company. The research hypotheses were tested using regression analysis. The results of the study prove that corporate governance can weaken the relationship between real earnings management and firm value. Meanwhile, the direct influence of earnings management on firm value was not found to have a negative relationship, but the results were positive. This research is expected to contribute to the development of theories related to earnings management behavior and corporate governance practices, namely agency theory. Other contributions can be used as input for investors in assessing the company, especially those related to the transparency of the company's financial reporting. Keywords: Abnormal Cash Flow From Operations; Corporate Governance; Firm Value; Agency Theory.